CLINICAL APPLICATION OF NIGHTINGALE’S THEORY INTO PRACTICE - yasmeen, samina; Iqbal, Javed; Hazara, Shair Mohammad; Akhtar, Nourin (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
Nurses are the backbone of any healthcare system. However, nurses are still struggling withmany challenges particularly in the developing world. One of the biggest challenge of today’snurse is the clinical application of nursing theoretical concepts into routine practice. Thepurpose of this scholarly paper is to explicitly describe the Nightingale nursing theory intoclinical practice in light of a clinical scenario particularly three core concepts (Bed andbedding, proper ventilation of ward, and proper hygienic dressing) in order to demonstrationthe evidence based practice in nursing care